Faktor Determinan yang Mempengaruhi Siklus Menstruasi (The Determinants of Menstrual Cycle) - Tri Suwarni (Indonesian Journal on Medical Science, 2015)
Abstract: In postpubertal women show changes cyclically repeated in the hypothalamic, pituitary, ovarian maturation and release of gametes causes of ovarian and uterine preparation to support a pregnancy if fertilization occurs. Factors related to the menstrual cycle include economic statu , anxiety and body mass index. This study aims to determine how the effect of economic status, anxiety and body mass index to the menstrual cycle students.This research was a Quantitative analytical observational study with cross sectional approach . The number of samples used 60 students Study Program Midwifery Diploma with sampling techniques : simple random sampling . Independent variables consisted of capabilities Economic Status, Anxiety and Body Mass Index. Dependent Variable : Menstrual Cycle. Data were analyzed with multiple linear regression analysis.There was a influence on the economic status of the menstrual cycle with a P value of 0.001 ( p <0.05 ). There is anxiety about the influence of the menstrual cycle with a P value of 0.001 ( p <0.05 ). There is the influence of BMI on the menstrual cycle of the menstrual cycle with P value of 0.001 ( p <0.05 ). In conclusion, there is a statistically significant effect of economic status , anxiety and body mass index to the menstrual cycle students .Keywords: economic status, anxiety, body mass index, menstrual cycle.Â Abstrak: Pada wanita pascapubertas memperlihatkan perubahan siklis yang berulang-ulang di dalam aksis hipotalamus, hipofisis, ovarium yang menyebabkan pematangan dan pelepasan gamet dari ovarium dan persiapan uterus untuk menunjang kehamilan jika terjadi fertilisasi. Faktor yang berhubungan dengan siklus menstruasi antara lainÂ  status ekonomi, kecemasan dan indeks massa tubuh. Penelitian ini bertujuan untuk mengetahui seberapa pengaruh status ekonomi, kecemasan dan indeks massa tubuh terhadap siklus menstruasi mahasiswa. Jenis penelitian kuantitatif analitik observasional dengan pendekatan cross sectional. Jumlah sampel yang digunakan 60 mahasiswa Progam Studi D III Kebidanan dengan teknik pengambilan sampel: simple random sampling. Variabel Independent terdiri dari kemampuan Status Ekonomi, Kecemasan Dan Indeks Massa Tubuh. Variabel dependent: Siklus Menstruasi. Data dianalisis dengan analisis regresi linier ganda. Ada pengaruh status ekonomi terhadap siklus menstruasi dengan nilai P value 0,001 (p< 0,05). Ada pengaruh kecemasan terhadap siklus menstruasi dengan nilai P value 0,001 (p< 0,05). Ada pengaruh IMT terhadap siklus mentruasi terhadap siklus menstruasi dengan nilai P value 0,001 (p< 0,05). Simpulannya, ada pengaruh secara statistik signifikan status ekonomi, kecemasan dan indeks massa tubuh terhadap siklus menstruasi mahasiswa.Kata Kunci : status ekonomi, kecemasan, indeks massa tubuh, siklus menstruasi.Â